MODIFIED ALGORITHM OF SMOOTHING/FILTERING THE DIFFERENTIAL GNSS OBSERVATIONS IN THE KINEMATIC POSITIONING MODE - Kondratyuk, Vasyliy; Zhelanov, Alexei; Ditskiy, Igor; Bessonov, Eugene (Proceedings of National Aviation University (archive), 2014)
The results of GNSS differential measurements code-phase smoothing/filtering modified algorithmdevelopment and validation have been presented for the mobile objects kinematic positioning. It is shown that theupdated algorithm allows considerable increasing of the positioning accuracy and obtaining a glide coordinatesolution in comparison with the analogs.